Alternativas de sistemas construtivos para condomínios residenciais horizontais - estudo de caso - Villar, Francelene Hermida Rezende (Universidade Federal de São Carlos, 2005)
Improvement in productivity is one important factor to tackle the increasing Brazilian housing deficit. Besides, civil construction industry holds strategic position in the development of the country due to its economical and social importance. In this scenery, the use of industrialized constructive systems has been more and more frequent, mainly by large construction companies and in buildings that need speed of execution. The main purpose of the current work is to show, from the perspective of important parameters to the construction of horizontal properties jointly owned (rationalization, quality, cost and performance, among others), a comparative analysis of Jet Casa constructive system (a system comprised of prefabricated panels, consisted of ceramic stones and armed concrete pillars) with constructive system in structural masonry with ceramic stones, traditionally used in such enterprises. This study is developed through a case study carried out for the construction of Jardins de Barcelona Joint Owned Property, in São José do Rio Preto, by Rodobens Negócios Imobiliários, consisted of 198 one-story double houses. Initially, some concepts related to the conception of horizontal properties jointly owned, as far as rationalization, quality and productivity are concerned, are briefly argued with theoretical base aim. Then, some constructive systems which are currently being used in Brazil for building residential units in a series are described and their main characteristics (project, materials, components and execution) are presented. This way, the current overview of this sector is provided. After this, Jet Casa constructive system is described in details: project, production, assembly and other characteristics (productivity, standardization of procedures, building site organization, costs, performance and rationalization). Briefly, structural masonry constructive process is also shown, in order to give the case study some foundation. Finally, from the perspective of important parameters to construction of horizontal properties jointly owned (rationalization, quality, cost and performance, among others), these two constructive processes are compared in order to be used in the enterprise in question. From this comparative analysis, the choice made by the company (still predominantly cost-oriented) and the parameters that influenced this decision are shown.
Keywords: Alvenaria; Alvenaria - sistemas construtivos; Alvenaria estrutural; Blocos de cerâmica.; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL